2018
DOI: 10.1002/gps.4917
|View full text |Cite
|
Sign up to set email alerts
|

The course of apathy in late‐life depression treated with electroconvulsive therapy; a prospective cohort study

Abstract: Objectives Apathy, a lack of motivation, is frequently seen in older individuals, with and without depression, with substantial impact on quality of life. This prospective cohort study of patients with severe late‐life depression treated with electroconvulsive therapy (ECT) aims to study the course of apathy and the predictive value of vascular burden and in particular white matter hyperintensities on apathy course. Methods Information on apathy (defined by a score of >13 on the Apathy Scale), depression sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, this specific group referred for and treated with ECT also indicates a strength of this study design, as all patients were severely ill. Moreover, we found that after ECT apathy symptoms may perpetuate in individual patients that were less responsive but this was not associated with WMH 35 . Thirdly, the risk of inadequate findings due to multiple testing.…”
Section: Strengths and Limitationsmentioning
confidence: 65%
See 1 more Smart Citation
“…However, this specific group referred for and treated with ECT also indicates a strength of this study design, as all patients were severely ill. Moreover, we found that after ECT apathy symptoms may perpetuate in individual patients that were less responsive but this was not associated with WMH 35 . Thirdly, the risk of inadequate findings due to multiple testing.…”
Section: Strengths and Limitationsmentioning
confidence: 65%
“…Moreover, we found that after ECT apathy symptoms may perpetuate in individual patients who were less responsive but this was not associated with WMH. 36 Fourth, is the risk of inadequate findings due to multiple testing. We addressed this point with correction for multiple testing, according to the Benjamini–Hochberg procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A pathy is defined as a lack of motivation and loss of interest in almost all daily activities and other persons, and is associated with a high caregiver burden. 1 Apathy can occur as part of a depressive disorder 2 and is particularly prevalent in patients with neurodegenerative diseases; however, apathy also frequently occurs in the older general population. 3 Both cerebrovascular and cardiovascular diseases are risk factors for apathy.…”
mentioning
confidence: 99%